Systematic Literature Review: Models of digital transformation in the public sector - Novianto Novianto (Policy & Governance Review, 2023)
Today's technological advances affect businesses and society, including the government. The success or failure of implementation is due to the ambiguity of the strategies used and the limited knowledge of the factors that influence them. Although some previous studies exist, their generalizability is limited. The purpose of this study is to provide a model from the existing literature to develop a strategy for successful digital transformation. This study utilized a systematic literature review and content analysis methodology. Scopus database was used to identify relevant articles using a search string and inclusion/exclusion criteria. Content analysis identified a model related to the research topic. The findings provide valuable insights and a model for future research and practical applications. The result is a model for implementing digital transformation in the public sector, which is divided into four elements: external, organizational, citizen, and technology. By using a more comprehensive approach, the resulting model should be better able to generalize. The elements and their sub-elements of the model will be a recommendation for managers at different levels to design strategies for managing digital transformation. Further research can explore quantitative methods to test the model and the generalizability of the results of this study.